The History of New World Leishmaniases From a Brazilian Perspective - Benchimol Jaime Larry (HoST, 2023)
This article addresses the leishmaniases in the Americas from a Brazilian perspective. The first cases of cutaneous and mucocutaneous leishmaniasis were described in 1909 in São Paulo. Latin American researchers gained international projection because of their work on this disease they considered autochthonous, which came to be known as American tegumentary leishmaniasis. But visceral leishmaniasis only emerged as a public health problem in the Americas in 1934 thanks to a new diagnostic technique for yellow fever. Zoonoses earned greater attention later, especially in the laboratory founded in 1965 at the Evandro Chagas Institute by Ralph Lainson and Jeffrey Shaw. Here we examine their connections with other teams and the resulting changes when they proved that parasite, vector, and host populations were much more heterogeneous than previously imagined. Technical innovations provided a better understanding of the distinct epidemiological characteristics of the illnesses caused by different Leishmania amid a backdrop of far-reaching transnational networks.